Control interno en el área de inventario en el Almacén Mega Lady Sports del cantón La Maná, período 2021. - Chimbo Troya, Stephanie Nallely (2023)
The internal control is a tool used to plan to control the operations that are made within the company, given the objectives that were presented in the research to the inventory area of the Mega Lady Sports store a diagnosis was made through a SWOT matrix which helped us to establish their strengths within which we found that the store has a variety of designs also has affordable prices for the consumer, as opportunities we have that the store increase offers on special dates. The methodology used for the development of this research had a qualitative and quantitative approach, it was a descriptive, documentary, field research that allowed us to observe in the facilities of the store how the inventories are managed and through the interview that was conducted with the owner, she stated that she has an appropriate place to store the merchandise. In the evaluation of internal control, the overall result was a confidence level of 82% and 18% risk, one of the reasons being that the warehouse does not audit the inventory area. With the results obtained through the diagnosis, the policies and procedures manual were created.